PENGARUH DIKLAT FUNGSIONAL, KOMPETENSI SDM DAN DISIPLIN KERJA TERHADAP PENGEMBANGAN KARIER PERSONEL POLSEK DAU KABUPATEN MALANG - jurnalmap map; Achmad Zainuddin; Muninghar ÔÇì; Fatimah Riswati (Program Pascasarjana Universitas Wijaya Putra Surabaya, 2020)
ABSTRACT The purpose of this research is 1) to know the simultaneous effect of functional training, human resource competence, and work discipline, to the development of career careers of DAU Police Sub-district of Malang Regency, 2) to know the partial influence of functional training, human resource competence, and work discipline, to the development of career careers of DAU Police Sub-district of Malang Regency, 3) To know the variables that have dominant influence to the development of career careers of DAU District Police Sector Malang. The results showed: 1) simultaneously functional training, human resource competence, and work discipline had a significant influence on the development of career careers of Malang District Police Sector, 2) Partially functional training, human resource competence, and work discipline have a significant influence on the development of career careers of DAU District Police Sector Malang, 3) Based on the results of the t test, it is known that the competence of human resources have a dominant influence on the development of career careers Police Sector of Malang Regency. Keywords: Functional Training, Human Resource Competence, Work Discipline and Career Development